2018
DOI: 10.1371/journal.pone.0202576
|View full text |Cite
|
Sign up to set email alerts
|

Detection of genetic alterations in gastric cancer patients from Saudi Arabia using comparative genomic hybridization (CGH)

Abstract: BackgroundThe present study was conducted to discover genetic imbalances such as DNA copy number variations (CNVs) associated with gastric cancer (GC) and to examine their association with different genes involved in the process of gastric carcinogenesis in Saudi population.MethodsFormalin-fixed paraffin-embedded (FFPE) tissues samples from 33 gastric cancer patients and 15 normal gastric samples were collected. Early and late stages GC samples were genotyped and CNVs were assessed by using Illumina HumanOmni1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 41 publications
1
15
0
1
Order By: Relevance
“…Samples from 33 gastric cancer patients were collected in Saudi Arabia and analyzed using CGH compared to 15 normal gastric samples from the same population. The study revealed frequently copy number gains within several chromosomal regions including 1q12 among the most frequent [83]. Other findings of 1q overrepresentation in various types of cancer were obtained by increasing in situ hybridized site numbers in lymphoma and myeloma [84] and hepatitis B virus-related hepatocellular carcinoma [85].…”
Section: Satii/iii Copy Gain In Stress Senescence and Cancermentioning
confidence: 71%
“…Samples from 33 gastric cancer patients were collected in Saudi Arabia and analyzed using CGH compared to 15 normal gastric samples from the same population. The study revealed frequently copy number gains within several chromosomal regions including 1q12 among the most frequent [83]. Other findings of 1q overrepresentation in various types of cancer were obtained by increasing in situ hybridized site numbers in lymphoma and myeloma [84] and hepatitis B virus-related hepatocellular carcinoma [85].…”
Section: Satii/iii Copy Gain In Stress Senescence and Cancermentioning
confidence: 71%
“…Some inhibitors designed as cancer therapeutics specifically targeting DSB repair proteins have been reported (52,53). However, DSB repair pathway selection and the associated factors remain poorly defined, especially regarding the mechanism by which H. pylori infection (62). The API2-MALT1 fusion gene was originally identified from a t(11;18)(q21;q21) translocation, a specific chromosomal abnormality that is found in mucosa-associated lymphoid tissue (MALT) lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of these two genes synergistically restored TGF-β responsiveness in gastric cancer cells and reduced tumor growth in vivo; biochemical analysis demonstrated that MEL1/PRDM16 interacted with SKI and inhibited TGF-β signaling by stabilizing the inactive Smad3-SKI complex on the promoter of TGF-β target genes ( Figure 3D) [251]. Similarly, PRDM16 high copy gain was also observed in a small cohort using CGH [252]. Otherwise, a more recent study showed that miR-214 was able to inhibit PRDM16 expression thus promoting the proliferation and migration of gastric cancer cells and enhancing the Warburg effect ( Figure 3H) [253].…”
Section: Prdm16mentioning
confidence: 72%